The Effects Of Customer Orientation, Competitor Orientation, And Promotion On The Marketing Performance Of Logistics Companies In Surakarta City - Utami, Eva Yuniarti; Nuvriasari, Audita (International Journal of Social Service and Research, 2023)
This study aims to explore the effects of customer orientation, competitor orientation, and promotion on marketing performance of logistics companies in Surakarta City. The research design employed a quantitative approach, utilizing a sample population of micro, small and medium-sized enterprises (MSMEs) in the expeditions or courier services sector. Data collection involved questionnaires and secondary data obtained from the Departement of Cooperatives, MSMEs, and Industry in Surakarta City. Descriptive statistics and regression analysis were used to analyze the data. The result of hypothesis testing revealed that customer orientatiom, competitor orientation, and promotion did not have a significant effect on the marketing performance of expedition services companies in Surakarta City. These findings contribute to the existing body knowledge and provide practical implications for logistics companie in Surakarta City to enhance their marketing strategies and overall performance. In conclusion, customer orientation, competitor oerientation, and promotion were found to be insignificant factors influencing the market performanceof logistics companies in Surakarta City. This reserach highlights the need for tailored strategies and futher investigations in the logistics industry. The implications of these findings provide insights for policy and practical in enhancing marketing strategies and suggest avenues for future studies in this context.